IMPROVING THE QUALITY OF ISLAMIC EDUCATION THROUGH AN INTEGRATED CURRICULUM - Shidqiyah; Rafika Nisa; Munawir; Al-Amin (CV. ADIBA AISHA AMIRA, 2024)
Islamic education today has to enrich its graduates not only with religious knowledge and comprehension of doctrines, but also equip them for the twenty first century society. The development of the integrated curriculum addresses this problem as it merges several disciplines while relating religious education to real- life situations. A literature study approach was employed in examining the issue under consideration. The findings indicate that an integrated curriculum approach can enhance active and constructive engagement of learners in the teachings of Islam which can create a relevant education that meets the expectations of contemporary society. However, the integration of an interdiciplinary curriculum does not bear fruits easily as there are some barriers such as lack of willingness to embrace change, scarcity of funds and the proper evaluation of students rated. Therefore, some strategies to overcome these challenges include effective training programmes, investment in resource development and improved coordination among stakeholders.